2013
DOI: 10.1007/s00726-013-1592-z
|View full text |Cite
|
Sign up to set email alerts
|

Beta-hydroxy-beta-methylbutyrate supplementation in health and disease: a systematic review of randomized trials

Abstract: Beta-hydroxy-beta-methylbutyrate (HMB), a metabolite of the branched-chain amino acid leucine, is extensively used by athletes and bodybuilders in order to increase strength, muscle mass and exercise performance. We performed a systematic review of the clinical literature on the effectiveness of HMB supplementation in healthy and pathological conditions (i.e. training programs, aging, acute and chronic diseases, and after bariatric surgery). We reviewed all clinical trials indexed in Medline that tested HMB su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
74
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 70 publications
0
74
0
2
Order By: Relevance
“…This effect is associated with the ability of Leu to activate mTORC1, which subsequently targets downstream signaling protein kinases such as 4E binding protein 1 (4EBP1) and p70S6K1, both of which facilitate translation initiation and stimulation of MPS (81). The discovery that Leu positively influences skeletal muscle metabolism makes it perhaps unsurprising that other molecules related to Leu, such as b-hydroxyb-methylbutyrate (b-HMB), a Leu metabolite, would also possess anabolic properties capable of influencing skeletal muscle protein turnover (82). Currently, b-HMB is a patentprotected compound with a number of applications but most relevant to this review are US patents: 5,348,979 (83), b-HMB is described as useful for promoting nitrogen retention in humans; and 6,031,000 (84), which, among other claims, is a compound stated as being used, ".to treat disease-associated wasting of an animal.." In addition, other patents list b-HMB (in combination with vitamin D) as being useful in the promotion of muscular function and strength (85).…”
Section: B-hydroxy-b-methylbutyratementioning
confidence: 97%
See 1 more Smart Citation
“…This effect is associated with the ability of Leu to activate mTORC1, which subsequently targets downstream signaling protein kinases such as 4E binding protein 1 (4EBP1) and p70S6K1, both of which facilitate translation initiation and stimulation of MPS (81). The discovery that Leu positively influences skeletal muscle metabolism makes it perhaps unsurprising that other molecules related to Leu, such as b-hydroxyb-methylbutyrate (b-HMB), a Leu metabolite, would also possess anabolic properties capable of influencing skeletal muscle protein turnover (82). Currently, b-HMB is a patentprotected compound with a number of applications but most relevant to this review are US patents: 5,348,979 (83), b-HMB is described as useful for promoting nitrogen retention in humans; and 6,031,000 (84), which, among other claims, is a compound stated as being used, ".to treat disease-associated wasting of an animal.." In addition, other patents list b-HMB (in combination with vitamin D) as being useful in the promotion of muscular function and strength (85).…”
Section: B-hydroxy-b-methylbutyratementioning
confidence: 97%
“…Currently, b-HMB is a patentprotected compound with a number of applications but most relevant to this review are US patents: 5,348,979 (83), b-HMB is described as useful for promoting nitrogen retention in humans; and 6,031,000 (84), which, among other claims, is a compound stated as being used, ".to treat disease-associated wasting of an animal.." In addition, other patents list b-HMB (in combination with vitamin D) as being useful in the promotion of muscular function and strength (85). In a recent systematic review of trials involving b-HMB in health and disease, Molfino et al (82) concluded that a meta-analysis of the effects of b-HMB supplementation in the elderly was not possible mostly because of the heterogeneity of trials and the lack of pure b-HMB being compared with a placebo; nevertheless, a recent review states that, "Essential amino acid (EAA) supplements, including. b-hydroxy b-methylbutyric acid (HMB) supplements, show some effects in improving muscle mass and function parameters (86)"; thus, the trials relevant to aging are reviewed here.…”
Section: B-hydroxy-b-methylbutyratementioning
confidence: 98%
“…Multiple studies have explored mechanisms that link HMB to muscle loss; it has been suggested that HMB can enhance protein synthesis via upregulation of anabolic signaling pathways and attenuate proteolysis via downregulation of catabolic signaling pathways (Hasselgren, 2014). Likewise, population surveys and clinical studies suggest that HMB treatment decreased muscle proteolysis (Baier et al, 2009) and muscle damage and increased fat-free mass gain both in young and older adults (Molfino, Gioia, Rossi Fanelli, & Muscaritoli, 2013). Indeed, HMB has been extensively used as an ergogenic aid, especially among bodybuilders and power athletes, who use it to promote exercise performance and skeletal muscle hypertrophy (Wilson et al, 2013a).…”
Section: Introductionmentioning
confidence: 97%
“…Many of these supplements have hazardous effects on health if taken without any considerations of the athlete's medical condition or without consulting a physician. One of the most widely used supplements is β-hydroxy-β-methylbutyrate (HMB) (Molfino et al 2013).…”
Section: Introductionmentioning
confidence: 99%